Solution-Induced Degradation of the Silicon Nanobelt Field-Effect Transistor Biosensors - Jung-Chih Lin; Zhao-Yu Zhou; Yi-Ching Cheng; I-Nan Chang; Chu-En Lin; Chi-Chang Wu (Biosensors, 2024)
Field-effect transistor (FET)-based biosensors are powerful analytical tools for detecting trace-specific biomolecules in diverse sample matrices, especially in the realms of pandemics and infectious diseases. The primary concern in applying these biosensors is their stability, a factor directly impacting the accuracy and reliability of sensing over extended durations. The risk of biosensor degradation is substantial, potentially jeopardizing the sensitivity and selectivity and leading to inaccurate readings, including the possibility of false positives or negatives. This paper delves into the documented degradation of silicon nanobelt FET (NBFET) biosensors induced by buffer solutions. The results highlight a positive correlation between immersion time and the threshold voltage of NBFET devices. Secondary ion mass spectrometry analysis demonstrates a gradual increase in sodium and potassium ion concentrations within the silicon as immersion days progress. This outcome is ascribed to the nanobelt’s exposure to the buffer solution during the biosensing period, enabling ion penetration from the buffer into the silicon. This study emphasizes the critical need to address buffer-solution-induced degradation to ensure the long-term stability and performance of FET-based biosensors in practical applications.